Somatic mosaicism for a PDHA1 mutation in a female with pyruvate dehydrogenase deficiency. - Ridout, C; Brown, R; Walter, J; Brown, G (2008)
Somatic mosaicism for a mutation in the X-linked PDHA1 gene was found in a girl who presented with manifestations of pyruvate dehydrogenase deficiency. Mutation in the PDHA1 gene was suggested by a mosaic pattern of E1alpha subunit immunostaining; however, initial screening of cDNA and the exons and intron-exon boundaries yielded only normal sequence, apart from a heterozygous 4 bp insertion in intron 10. This was considered to be a polymorphism as it is also present in her unaffected mother who has normal enzyme activity and uniform E1alpha immunostaining in fibroblasts. Detailed genetic analysis, which included isolation of cloned fibroblasts expressing the mutant X chromosome, resulted in the identification of a base substitution in the acceptor splice site of intron 9 which leads to activation of a cryptic upstream splice site. The proportion of cells expressing the mutation was then determined by direct analysis of the X-inactivation pattern. Genetic diagnosis in this unique case of PDHA1 somatic mosaicism was complicated by the absence of an abnormal transcript in primary fibroblasts, the presence of three different alleles and an X-inactivation pattern favouring expression of the normal, paternal, X chromosome. Although the mutation was only present in a proportion of cells, and only expressed in a subset of these due to random X-inactivation, the resulting enzyme defect was sufficient to be clinically apparent.